Synthesis of pyrano[3, 2-c]quinolones and furo[3, 2-c]quinolones via acid-catalyzed tandem reaction of 4-hydroxy-1-methylquinolin-2(1H)-one and propargylic alcohols. Issue 33 (21st July 2022) - Yin, Haiting; Wu, Yunjun; Gu, Xiaoxia; Feng, Zhijun; Wang, Meifang; Feng, Dexiang; Wang, Ming; Cheng, Ziyang; Wang, Shaoyin
Abstract : Two acid-catalyzed tandem reactions between 4-hydroxy-1-methylquinolin-2(1 H )-one and propargylic alcohols are described. Abstract : Two acid-catalyzed tandem reactions between 4-hydroxy-1-methylquinolin-2(1 H )-one and propargylic alcohols are described. Depending mainly on the propargylic alcohol used, these tandem reactions proceed via either a Friedel–Crafts-type allenylation followed by 6- endo -dig cyclization sequence to form pyrano[3, 2- c ]quinolones or a Friedel–Crafts-type alkylation and 5- exo -dig ring closure sequence to afford furo[3, 2- c ]quinolones in moderate-to-high yields. The pyrano[3, 2- c ]quinolones products could be further transformed to tetracyclic 4, 9-dihydro-5 H -cyclopenta[ lmn ]phenanthridin-5-one derivatives.